Análise do desempenho de sistemas de iluminação lateral em edifícios comerciais na zona bioclimática 2 - Gabriel, Elaise (2020)
Numerous buildings have high rates of waste of electricity, as well as opportunities to save energy by not considering bioclimatic, passive and / or active strategies. In commercial buildings, daylight plays a major role because it is abundantly available during the occupation hours of these buildings. However, artificial lighting is responsible for a large portion of the energy consumption, mainly because these buildings do not make the integrated use of both forms of lighting. The use of daylight, in addition to providing appropriate illuminance levels for the performance of human activities, also reduces the need for the use of artificial light, which can be efficiently controlled by lighting systems, correct sizing of openings and use of shading devices, thus interfering with the building's thermal gains and total energy consumption. This work aims to evaluate the thermal performance of a commercial room, located at the Bioclimatic Zone 2, within the influence of the integrated use of natural and artificial light with air conditioning, with different types of glass and opening shading devices. The methodology was based on the evaluation and comparison of the luminous and energetic performance of models with different variables, through computational simulation in the DesignBuilder. The results showed that glasses with VLT of 0.13 and 0.52 show a reduction in the levels of UDI with the use of shading, whereas glasses with a higher VLT show an increase in the levels of UDI with the use of brises. In addition, it was possible to identify the impact of using daylighting on total energy consumption, through integrated simulations, about 79% savings by artificial lighting. Another result was the use of shading devices, which allowed a reduction of up to 88.45% in energy consumption by air conditioning. The use of artificial lighting system control through sensors provided a reduction in energy consumption with artificial lighting as well as influencing the thermal behavior of the air conditioner. This work allowed the incentive for the inclusion of strategies to reduce consumption and improve the energy efficiency of buildings.